Decline in Business Activity on the Zimbabwe Stock Exchange: A Sign of a Bloodbath on the Zimbabwe Economy (2014) (Global Journal of Management and Business Research, 2015)
The mission in this Paper -Decline in business activity at the Zimbabwe activity at the Zimbabwe Stock Exchange: A sign of a limping economy is to measure the decline in the trade in counters during the period September -October 2014. After the discussion of the results, the Author will proffer a Summary, Conclusion and Recommendations to wrap up the discourse.
Keywords: decline trade; counters; zimbabwe stock exchange; limping economy